Volume Kerja dan Waktu Penggilingan Tongkol Jagung pada Ukuran Produk/ Morfologi dalam Proses Ball Mill - Ahmad Nurul Muttaqin; Uswatul Hasanah Mihdar (Politeknik Negeri Ujung Pandang, 2023)
The use of corncob powder is very wide in various industrial fields, namely as a source of dietary fiber, the basic material for making bio-plastics, partial replacement of cement in the manufacture of concrete, functional chemicals, oyster mushroom cultivation media. The most efficient method in producing corncob powder is the Ball Mill Process. The purpose of this study was to evaluate the effect of working volume and milling time on the characteristics of corn cob powder. The research procedures include specimen preparation (including cutting and drying processes) and milling processes. The results obtained were then characterized using a scanning laser microscope (LSM) to analyze the morphology and size of the product, lower working volume results in a smaller powder production with a needle-like sharp edge morphology and a higher work volume also results in a powder that has a blunt edge morphology. Although working volume can potentially be used to control particle size, this parameter has a direct effect on powder yield. As for the long milling time, it produces a smaller powder size than the faster milling time.Â